Problem of „Blockade“ and „Removal of Blockade“ of Building Land in the Republic of Serbia - Martinović, Aleksandar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The area of planning and building is an extremly important part of social life in each country, as well as in the Republic of Serbia. This area is regulated by administrative legal norms in large extend. After the adoption Act on the planning and building in 2009, the Constitutional Court declared unconstitutional the provision of Article 103, Paragraph 1 of the Law on the planning and building by his Decision No. IUZ-68/2013 from 10th October 2013. This decision led to a „blockade“ of building land in the Republic of Serbia. The exit from that situation was enabled by passing the Law on Amendments to the Law on Planning and Building in 2014. This important area of social life was significantly improved by those provisions. It could be expected that those roles will be usefull not only for citisens, but also for the Serbian economy as a whole Key words: planning and building, blockade and removal of blockade of building land, administrative procedure, authorization for building